Infrastructure expansion, tourism, and electoral outcomes - Adrian Mehic (Research Institute of Industrial Economics (IFN), 2024)
This paper examines the electoral impact of increased foreign tourism, using data from Croatia. Exploiting exogenous variation in travel times to coastal municipalities from improved road infrastructure, I show that foreign tourism reduces nationalist voting and increases the center-left vote share. This effect is partly due to manufacturing spillovers and demographic shifts within municipalities. Further complementing these findings, individual-level survey data indicates that workers within the hospitality sector are more likely to hold left-wing views. I further show that this is likely driven by economic concerns, rather than the diffusion of socially liberal views.
Keywords: D72; F63; L83; O18; Z32; 330; Infrastructure; Tourism; Voting; Nationalism